Analysis of Students Metacognitive Skill in Solving Problem on Guided Inquiry Learning Model - Bahiyah, Lumiyatun; Sudarmin, Sudarmin; Hartono, Hartono (Postgraduate, Universitas Negeri Semarang, Indonesia, 2019)
Metacognitive skill is fundamental in achieving understanding of science concepts and developing problem solving skills. Guided inquiry learning model can develop metacognition and problem solving skill. Research was conducted by mix method approach and concurrent triangulation strategy. The purpose of this study is to analyze metacognition and problem solving skills and analyze the relationship between metacognition skills and problem solving abilities after following the guided inquiry learning models. The result showed that 72,2% of students had metacognitive skill with growing very well category, and 27,8% belong to the category well developed. The most dominant component of metacognition is planning with subcomponent determine goal of problem. According to the result of problem solving test, it shows that the most students included in the good category (44,4%), the most dominant indicator is understanding the problem.